Nonlinear impact of remittances on financial inclusion in developing countries: Does governance quality matter? - Ahsan Aslam Khan; Mohammad Helmi Bin Hidthiir; Tan Bee Wah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This paper explores the relationship between remittance inflows and financial inclusion in developing countries, emphasizing the crucial role of governance quality. Using dynamic panel data methods on data from 2011-2021 across 89 countries, the study reveals a nonlinear relationship between remittances and financial inclusion. We employed GMM approach to address endogeneity issues and mediation model analysis while using Stata software. Notably, remittance inflows have a negative impact on financial inclusion in countries with lower levels of remittances but a positive impact in countries with higher levels of remittances. Furthermore, the study demonstrates that the effect of remittances on financial inclusion is significantly mediated by governance quality. Good governance enhances the positive impact of remittances, transforming them into a powerful tool for promoting financial inclusion. Conversely, in countries with weak governance, remittances enhance financial exclusion by increasing mistrust in financial institutions. These findings highlight the need to improve governance structures to maximize the developmental potential of remittances.
Keywords: 330; Remittances; financial inclusion index; governance quality; governance index